Impact of cash based interventions in livelihood recovery of waterlogging affected community in Satkhira district - Chakraborty, Tapan Kumar (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2016.